Pengaruh Store Atmosphere, Harga dan Kelengkapan Produk Terhadap Keputusan Pembelian Konsuemn Pada Farina Femme Beauty Store - 'Illiyyun, Labibah (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2025)
The development of the cosmetics industry has led to increasingly fierce and competitive business competition. This demands business actors to determine the right strategies to remain competitive. One such strategy is to develop innovations, such as focusing on store atmosphere and environment. Additionally, pricing and product variety are important marketing tools to attract consumer interest. This study aims to determine the influence of store atmosphere, pricing, and product variety on purchasing decisions, with Farina Femme Beauty Store as the research object. The study employs a quantitative approach using a survey method and SPSS as the analytical tool. The primary data was collected through respondents' answers to a questionnaire comprising 31 questions. Data collection was conducted by distributing the questionnaire to respondents who had purchased products at Farina Femme Beauty Store. The sampling technique used was probability sampling with the simple random sampling method, calculated using Lemeshow formula, resulting in a total sample of 100 respondents.The results of this study indicate a significant partial effect of store atmosphere on purchasing decisions, with a tvalue of 4.427 > ttable of 1.988. Pricing has a negative partial influence on purchasing decisions, with a tvalue of -4.326 < ttable of 1.988. Product variety has a significant partial effect, with a tvalue of 10.096 > ttable of 1.988. Simultaneously, store atmosphere, pricing, and product variety significantly influence purchasing decisions, with an Fvalue of 86.566 > Ftable of 2.70. It is hoped that Farina Femme Beauty Store can enhance and maintain its store atmosphere, pricing, and product variety to attract more consumers and improve purchasing decisions.